Trypanosoma Species in Small Nonflying Mammals in an Area With a Single Previous Chagas Disease Case - Dario, Maria Augusta; Lisboa, Cristiane Varella; Xavier, Samanta Cristina das Chagas; D’Andrea, Paulo Sérgio; Roque, André Luiz Rodrigues; Jansen, Ana Maria (Frontiers in Cellular and Infection Microbiology, 2022)
Trypanosomatids are hemoflagellate parasites that even though they have been increasingly studied, many aspects of their biology and taxonomy remain unknown. The aim of this study was to investigate the Trypanosoma sp. transmission cycle in nonflying small mammals in an area where a case of acute Chagas disease occurred in Mangaratiba municipality, Rio de Janeiro state. Three expeditions were conducted in the area: the first in 2012, soon after the human case, and two others in 2015. Sylvatic mammals were captured and submitted to blood collection for trypanosomatid parasitological and serological exams. Dogs from the surrounding areas where the sylvatic mammals were captured were also tested for T. cruzi infection. DNA samples were extracted from blood clots and positive hemocultures, submitted to polymerase chain reaction targeting SSU rDNA and gGAPDH genes, sequenced and phylogenetic analysed. Twenty-one wild mammals were captured in 2012, mainly rodents, and 17 mammals, mainly marsupials, were captured in the two expeditions conducted in 2015. Only four rodents demonstrated borderline serological T. cruzi test (IFAT), two in 2012 and two in 2015. Trypanosoma janseni was the main Trypanosoma species identified, and isolates were obtained solely from Didelphis aurita. In addition to biological differences, molecular differences are suggestive of genetic diversity in this flagellate species. Trypanosoma sp. DID was identified in blood clots from D. aurita in single and mixed infections with T. janseni. Concerning dogs, 12 presented mostly borderline serological titers for T. cruzi and no positive hemoculture. In blood clots from 11 dogs, T. cruzi DNA was detected and characterized as TcI (n = 9) or TcII (n = 2). Infections by Trypanosoma rangeli lineage E (n = 2) and, for the first time, Trypanosoma caninum, Trypanosoma dionisii, and Crithidia mellificae (n = 1 each) were also detected in dogs. We concluded that despite the low mammalian species richness and degraded environment, a high Trypanosoma species richness species was being transmitted with the predominance of T. janseni and not T. cruzi, as would be expected in a locality of an acute case of Chagas disease.